2021
DOI: 10.1177/15248380211021788
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Sensitivity in Interventions Aiming to Reduce or Prevent Intimate Partner Violence During Pregnancy: A Scoping Review

Abstract: Intimate partner violence (IPV) around the time of pregnancy is a recognized global health problem. Ethnic minorities and immigrant pregnant women experiencing IPV require culturally responsive health services. The aim of this scoping review was to identify aspects of cultural sensitivity in interventions to prevent or reduce IPV among ethnic minorities and immigrant pregnant women in high-income countries. Eight databases were searched in November 2019. Any type of scientific research, quantitative, qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…If developmental outcomes are predefined, we cannot ensure that operationalizations of developmental outcomes in our search is inclusive enough to accurately cover all outcomes examined in the prenatal IPV literature. Thus, we adopted a broad scoping search strategy so that all prenatal IPV exposure studies are identified, and the studies on child developmental outcomes can be reviewed based on the inclusion and exclusion criteria, consistent with the search strategies used in other high quality scoping review studies (e.g., Henriksen 2023; Zhang et al, 2022). The PubMed search terms were translated to the other databases.…”
Section: Methodsmentioning
confidence: 99%
“…If developmental outcomes are predefined, we cannot ensure that operationalizations of developmental outcomes in our search is inclusive enough to accurately cover all outcomes examined in the prenatal IPV literature. Thus, we adopted a broad scoping search strategy so that all prenatal IPV exposure studies are identified, and the studies on child developmental outcomes can be reviewed based on the inclusion and exclusion criteria, consistent with the search strategies used in other high quality scoping review studies (e.g., Henriksen 2023; Zhang et al, 2022). The PubMed search terms were translated to the other databases.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this review is to examine the use of cultural tailoring and CML education in IPV interventions for Black adolescents. We investigated standard aspects of each program (e.g., content, sample, research design, and outcomes) for intervention-centered scoping reviews (e.g., Henriksen et al, 2021). In addition, we sought to identify the definitions and elements of cultural tailoring, as well as any inclusion of media literacy.…”
Section: Methodsmentioning
confidence: 99%
“…Intimate partner violence (IPV) against women is a global public health and serious human rights abuse issue (Devries et al, 2013). It has permeated all levels of society (O’Doherty et al, 2015), affecting individuals and families from different races, religions, and economic levels, but because of cultural differences, awareness of and resistance to IPV varies greatly (Bent-Goodley, 2007; Henriksen et al, 2023; Postmus et al, 2020). It is likely to result in some family instability and social conflict if not handled properly.…”
Section: Introductionmentioning
confidence: 99%